(untitled) (Research, Society and Development, 2021)
The objective of this study was to analyze the efficiency and agreement between coprological techniques in the diagnosis of enteroparasites in patients with HIV in the Upper Pantanal. Fecal samples were collected and analyzed from 28 patients with the HIV virus, in which the techniques used were spontaneous sedimentation, the centrifugal-fluctuation method in sucrose solution and the technique with Safranin staining. In Hoffman’s technique, the greatest positivity of enteroparasites was that observed for the protozoan Blastocystis spp. the frequency of 52.38% is common, followed by Giardia lamblia with 21.47%. In Sheather the greatest positivity was also Blastocystis spp. 63.8%, followed by Giardia lamblia 33.33%. The technique using the Safranina dye possible identification of four protozoa that were not visualized in the sedimentation and flotation techniques. The principle that the flotation and sedimentation techniques differ in the diagnosis is not consistent with the results observed in this study, given that both techniques were efficient in detecting protozoa, such as Blastocystis spp. and Giardia lamblia, regardless of whether or not they are in saturated solutions. Therefore, to ensure better results, the association of techniques always results in greater reliability, especially when using different fundamental techniques.